Stakeholder engagement in the study and management of invasive alien species - Shackleton, Ross T; Adriaens, Tim; Brundu, Giuseppe; Dehnen-Schmutz, Katharina; Estévez, Rodrigo A; Fried, Jana; Larson, Brendon M H; Liu, Shuang; Marchante, Elizabete; Marchante, Hélia; Moshobane, Moleseng C; Novoa, Ana; et al. (Journal of environmental management, 2019)
Invasive alien species are a major driver of global environmental change and a range of management interventions are needed to manage their effects on biodiversity, ecosystem services, human well-being and local livelihoods. Stakeholder engagement is widely advocated to integrate diverse knowledge and perspectives in the management of invasive species and to deal with potential conflicts of interest. We reviewed the literature in the ISI Web of Science on stakeholder engagement (the process of involving stakeholders (actors) in decision making, management actions and knowledge creation) in invasion science to assess and understand what has been done (looking at approaches and methodologies used, stakeholders involved, and outcomes from engagement) and to make recommendations for future work. Research on stakeholder engagement in invasion science has increased over the last decade, helping to improve scientific knowledge and contributing towards policy formulation and co-implementation of management. However, many challenges remain and engagement could be made more effective. For example, most studies engage only one stakeholder group passively using questionnaires, primarily for assessing local knowledge and perceptions. Although useful for management and policy planning, these stakeholders are not active participants and there is no two-way flow of knowledge. To make stakeholder involvement more useful, we encourage more integrative and collaborative engagement to (1) improve co-design, co-creation and co-implementation of research and management actions; (2) promote social learning and provide feedback to stakeholders; (3) enhance collaboration and partnerships beyond the natural sciences and academia (interdisciplinary and transdisciplinary collaboration); and (4) discuss some practical and policy suggestions for improving stakeholder engagement in invasion science research and management. This will help facilitate different stakeholders to work better together, allowing problems associated with biological invasions to be tackled more holistically and successfully.
Keywords: zavlečené druhy; Research Design; Biodiversity; Animals; lidé; účast zainteresovaných stran; Humans; zvířata; Introduced Species; Decision Making; Stakeholder Participation; výzkumný projekt; biodiverzita; rozhodování